Strategi Pengembangan Potensi Desa Melalui Peran Pemuda Menuju Desa Berdaya Dan Desa Wisata: Strategy For Developing Village Potential Through Role Youth Towards A Powerful Village and Tourism Village - Dhalia Soetopo; Miskawi Miskawi; Hervina Nurullita; Siti Holifatun (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Kaliploso is a village in Cluring District, Banyuwangi Regency which has a lot of potential, one of which is a Horticultural Village. The existing potentials must be developed to become village-based tourist destinations in order to improve the community's economy. Village development efforts must involve many parties, one of which is the role of youth. Youth as the spearhead towards change with all the potential it has. The method used is qualitative research. The data collectors used include observation, interviews and documentation. Based on the results and discussion, the existence of Karangtaruna contributes a lot to the development of Kaliploso Village as an empowered village and a tourist village. The youth together with the village government produced various creative ideas packaged in a festival agenda ranging from agriculture, animal husbandry, health, culture and religion. Kaliploso adalah sebuah desa di Kecamatan Cluring Kabupaten Banyuwangi yang memiliki banyak potensi salah satunya sebagai Desa Hortikultura. Potensi-potensi yang ada harus dikembangkan untuk menjadi destinasi wisata berbasis desa agar dapat memperbaiki ekonomi masyarakat. Upaya pengembangan desa harus melibatkan banyak pihak salah satunya peran pemuda. Pemuda sebagai ujung tombak menuju perubahan dengan segala potensi yang dimilikinya. Metode yang digunakan penelitian kualitatif. Pengumplan data yang diunakan antara lain observasi, wawancara dan dokumentasi. Berdasarkan hasil dan pembahasan, keberadaan Karangtaruna banyak memberikan konstribusi bagi pengembangan Desa Kaliploso sebagai desa berdaya dan desa wisata. Dari pemuda bersama pemerintah desa menghasilkan berbagai ide kreative dikemas agenda festival mulai dari pertanian, peternakan, kesehatan, budaya dan keagamaan